2011
DOI: 10.1097/pcc.0b013e3181fe38f5
|View full text |Cite
|
Sign up to set email alerts
|

A trial of methadone tapering schedules in pediatric intensive care unit patients exposed to prolonged sedative infusions*

Abstract: Patients who received infusions of fentanyl for at least 5 days were just as likely to complete a low-dose methadone taper as a high-dose methadone taper. Because of the risks of both withdrawal and oversedation with any fixed methadone schedule, the methadone dose must be adjusted according to each patient's response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
100
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(100 citation statements)
references
References 47 publications
0
100
0
Order By: Relevance
“…1,4,8,16,17,2535 Subjects with longer PICU or hospital lengths of stay, 8,29 more ventilator days, 8,29 and longer ECMO therapy 4,28 were more likely to experience IWS. In one paper, subjects in a randomized trial of methadone-facilitated weaning were more likely to experience treatment failure with longer PICU lengths of stay, particularly after receiving fentanyl for ≥9 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,4,8,16,17,2535 Subjects with longer PICU or hospital lengths of stay, 8,29 more ventilator days, 8,29 and longer ECMO therapy 4,28 were more likely to experience IWS. In one paper, subjects in a randomized trial of methadone-facilitated weaning were more likely to experience treatment failure with longer PICU lengths of stay, particularly after receiving fentanyl for ≥9 days.…”
Section: Resultsmentioning
confidence: 99%
“…In one paper, subjects in a randomized trial of methadone-facilitated weaning were more likely to experience treatment failure with longer PICU lengths of stay, particularly after receiving fentanyl for ≥9 days. 29 In two small studies, subjects experiencing IWS received at least 10 days of opioid or benzodiazepine therapy. 34,35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Bowens et al compared the weaning of opioids with low and high doses of methadone, showing no difference between the two approaches. 61 Other studies demonstrated the implementation of a protocol for the management of abstinence syndrome reduces the time and dosage of those drugs, while the WAT-1 scale has a good performance evaluating abstinence. [62][63][64][65][66] Fernandez-Carrión et al showed that reductions of 10% in the doses of methadone every day implied in no increase in the incidence of signs and symptoms of abstinence, needs of morphine rescue therapy, or excess sedation.…”
Section: Resultsmentioning
confidence: 99%
“…Weaning strategies ranging from 10 days to several months have been evaluated in observational (retrospective and prospective) studies (132136). Two negative RCTs evaluated methadone weaning in 5 vs. 10 days (137) and a high- vs. low-dose methadone schedule in children (138). And while target drug levels for sedative and opioid dependence have been established for adults, they are lacking for children, as are PK data.…”
Section: Adverse Effectsmentioning
confidence: 99%